High Inflammatory Tendency Induced by Malignant Stimulation Through Imbalance of CD28 and CTLA-4/PD-1 Contributes to Dopamine Neuron Injury - Dong L; Zheng YM; Luo XG; He ZY (Dove Medical Press, 2021)
Li Dong,1 Yu-Min Zheng,2 Xiao-Guang Luo,3 Zhi-Yi He2 1Department of Neurology, The Fourth Affiliated Hospital of China Medical University, Shenyang, People’s Republic of China; 2Department of Neurology, The First Affiliated Hospital of China Medical University, Shenyang, People’s Republic of China; 3Department of Neurology, The First Affiliated Hospital of South University of Science and Technology, The Second Clinical College of Jinan University, Shenzhen People’s Hospital, Shenzhen, People’s Republic of ChinaCorrespondence: Xiao-Guang LuoDepartment of Neurology, The First Affiliated Hospital of South University of Science and Technology, The Second Clinical College of Jinan University, Shenzhen People’s Hospital, Shenzhen, People’s Republic of ChinaEmail guanche537@126.comZhi-Yi HeDepartment of Neurology, The First Affiliated Hospital of China Medical University, Shenyang, People’s Republic of ChinaEmail yizizhan40559@163.comBackground: Parkinson’s disease is a common neurodegenerative disease in the elderly. The incidence of various cancers in Parkinson’s disease patients is significantly lower than in healthy people. Parkinson’s disease patients are individuals with a high tendency for inflammation, whose peripheral immune system is represented in an activated state. We hypothesized that the hyperinflammatory predisposition of Parkinson’s disease patients is pathogenic.Methods: DBA/1 mice were used to simulate “highly inflammatory individuals”, and the carcinogen DEN was used to induce malignancy. Hematoxylin & eosin (H&E) staining was used to observe the formation of lung tumors. Apoptosis of neurons was observed by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining. Immunohistochemistry and flow cytometry were used to observe CD4, CD28, major histocompatibility complex II (MHCII), cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), and programmed death 1 (PD-1). The ionized calcium binding adaptor molecule-1 (IBA-1) + inducible nitric oxide synthase (iNOS) was used to label M1 microglia, and IBA-1 + arginase 1 (Arg1) was used to label M2 microglia by immunofluorescence. The expression of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and anti-inflammatory cytokines IL-10 and IL-4 was detected by ELISA.Results: DBA/1 mice with high inflammatory tendency showed a continuous increase of peripheral inflammation, promoting intracranial inflammation, decreasing the tumor incidence and increasing the neurodegeneration under induction of malignant change. CD28 and CTLA-4/PD-1 reduced the T-cell-dominated inflammatory response, reduced the intracerebral inflammatory response, protected from neurodegeneration, and increased the incidence of tumor. Combination of CTLA-4 and PD-1 blocker can overactivate T cells, worsen peripheral and intracranial inflammation, reduce the incidence of tumor, cause damage to dopamine neurons, and promote the occurrence of neurodegeneration.Conclusion: High inflammatory tendency induced by malignant stimulation through the imbalance of CD28 and CTLA-4/PD-1 leads to dopamine neuron injury.Keywords: high inflammatory tendency, malignant stimulation, CD28, CTLA-4/PD-1, dopamine neuron injury